Sources of international cost data - Humphreys, Kenneth (Acta Structilia, 1997)
A good estimator can readily develop the estimate for a project in the home country, but such is not always the case for other nations. While cost engineers, quantity surveyors and project managers are generally very familiar with major sources of cost data in their own country, they are often unaware of useful sources of cost data and related information in other countries. This problem is exacerbated by lack of time to perform a proper search, publications in various languages, and lack of information about key factors that can impact the estimate for particular geographic locations.